Coronary artery computed tomography as the first-choice imaging diagnostics in patients with high pre-test probability of coronary artery disease (CAT-CAD) - Rudziński, Piotr N.; Kruk, Mariusz; Demkow, Marcin; Dzielińska, Zofia; Pręgowski, Jerzy; Witkowski, Adam; Rużyłło, Witold; Kępka, Cezary (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction: The primary diagnostic examination performed in patients with a high pre-test probability of coronary artery disease (CAD) is invasive coronary angiography. Currently, approximately 50% of all invasive coronary angiographies do not end with percutaneous coronary intervention (PCI) because of the absence of significant coronary artery lesions. It is desirable to eliminate such situations. There is an alternative, non-invasive method useful for exclusion of significant CAD, which is coronary computed tomography angiography (CCTA). Aim : We hypothesize that use of CCTA as the first choice method in the diagnosis of patients with high pre-test probability of CAD may reduce the number of invasive coronary angiographies not followed by interventional treatment. Coronary computed tomography angiography also seems not to be connected with additional risks and costs of the diagnosis. Confirmation of these assumptions may impact cardiology guidelines. Material and methods : One hundred and twenty patients with indications for invasive coronary angiography determined by current ESC guidelines regarding stable CAD are randomized 1 : 1 to classic invasive coronary angiography group and the CCTA group. Results : All patients included in the study are monitored for the occurrence of possible end points during the diagnostic and therapeutic cycle (from the first imaging examination to either complete revascularization or disqualification from the invasive treatment), or during the follow-up period. Conclusions : Based on the literature, it appears that the use of modern CT systems in patients with high pre-test probability of CAD, as well as appropriate clinical interpretation of the imaging study by invasive cardiologists, enables precise planning of invasive therapeutic procedures. Our randomized study will provide data to verify these assumptions.